Measurement of the moving objects’ bearing by coherent integration of the spectral components of signals in the passive sonar - S. R. Heister; D. N. Nguyen (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The method of measuring bearing (azimuth) of a moving surface (underwater) object in the passive sonar is described. This method is considered to be a modification of signals phase comparing method. It is based on the measurement of the delay time between signals received at different signal reception point. A distinctive feature of this method is the use for signal processing method of coherent accumulation of the spectral components of the received signal, developed by the authors. This method provides increase signal/noise ratio in the reception channels, therefore decrease errors of measuring bearing in the passive sonar.